2005
DOI: 10.1111/j.1365-3091.2005.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires and seasonal aridity recorded in Late Cretaceous strata from south‐eastern Arizona, USA

Abstract: Lithostratigraphic and organic chemostratigraphic studies of fluvial/lacustrine sediments in the Late Cretaceous Fort Crittenden Formation in south‐eastern Arizona USA, reveal changes in palaeoclimate and tectonics as well as associated fluctuations in lake level. The lower Fort Crittenden is dominated by marginal wetland to deep‐water lake deposits, whereas the upper Fort Crittenden is characterized by wetland to deltaic deposits. Abundance of polycyclic aromatic hydrocarbons (PAH) and reflectance of fusinite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Increasing number of hydrocarbon rings within the compound reflects an increased temperature of formation. Dominance of 2-3-ringed forms in the succession is consistent with the low-moderate intensity fires, whereas high-intensity fires produce elevated concentrations of 5-6-ringed forms 32 . It has been noticed that fluorene and phenanthrene are dominantly present in all the samples and both these forms possess three-ringed aromatic structures.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Increasing number of hydrocarbon rings within the compound reflects an increased temperature of formation. Dominance of 2-3-ringed forms in the succession is consistent with the low-moderate intensity fires, whereas high-intensity fires produce elevated concentrations of 5-6-ringed forms 32 . It has been noticed that fluorene and phenanthrene are dominantly present in all the samples and both these forms possess three-ringed aromatic structures.…”
supporting
confidence: 49%
“…moss) remained unaffected combustion in an ambient O 2 conditions 2 at temperatures of ~800°C. The relative concentration of individual PAH compounds is linked with the intensity of the wildfire as well as the type of organic influx 32 . Increasing number of hydrocarbon rings within the compound reflects an increased temperature of formation.…”
mentioning
confidence: 99%
“…It has been shown that charcoal can be created and persist at temperatures of the order of 1,000°C (6) and that even delicate charred plant parts (e.g., moss) remain when combusted in ambient O 2 conditions at temperatures of Ϸ800°C (21). The relative concentrations of individual pPAHs are known to be related to either the intensity of the wildfire or the type of fuel (22). Increasing number of hydrocarbon rings within the compound reflect an increased temperature of formation.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing number of hydrocarbon rings within the compound reflect an increased temperature of formation. A dominance of 2-3 ringed forms is typically consistent with low-moderate intensity fires whereas hotter fires will produce elevated concentrations of 5-6 ringed forms (22). The pPAH signature (i.e., the variety of pPAHs and their relative proportions to one another) in the rock layers (Table S1) was analyzed to assess the likely temperature of formation of the pPAHs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These gases are emitted to air, and after various physical and chemical transformation processes in the atmosphere, they precipitate as acid rain elsewhere, as carbonic acid, sulfuric acid and nitric acids. The combustion remains, left in the wildfire area are mineralized, alkaline ash products, rich in base cations, phosphate, chlorides, heavy metals (Eriksson et al 2003;Kelly et al 2006) and pyrolytic polycyclic aromatic hydrocarbons, PAH (Finkelstein et al 2005).…”
Section: Introductionmentioning
confidence: 99%